Ideal management of social assistance funds as a prevention and mitigation effort corruption - Parameshwara, Parameshwara; Riza, Khairul (Journal of Multidisciplinary Academic and Practice Studies, 2023)
Purpose: The purpose of this study is to analyze and determine the ideal legal arrangements for the management of social assistance funds in order to prevent corruption, as well as to examine effective efforts to prevent and overcome corruption practices in the distribution and use of such funds. Research Methodology: This study employs a normative juridical method combined with statutory, conceptual, and sociological juridical approaches to provide a comprehensive understanding of both legal principles and their social implementation. Results: The findings indicate that the ideal arrangement for social assistance fund management must incorporate positive legal principles as formulated by John Austin, including the establishment of clear authorities through legislative or governmental institutions, ensuring that the law reflects state sovereignty, setting explicit rules that bind all parties, and providing a foundation for strong and effective enforcement of the law. These aspects ensure that the law acts as an instrument of control over corruption. Conclusions: Preventing and combating corruption in social assistance requires integrating Jeremy Bentham’s utilitarianism, which prioritizes maximizing social welfare, ensuring fair benefit distribution, and embedding transparency and accountability in every decision-making process. Limitations: This study is limited to a normative juridical framework and does not include empirical fieldwork, which may restrict practical insights into current implementation challenges. Contribution: This study contributes theoretically by offering a legal-philosophical foundation for regulating social assistance funds and practically by proposing frameworks that policymakers can adopt to strengthen preventive and repressive mechanisms against corruption.